2012
DOI: 10.1016/j.neuron.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoids Shape Accumbal Encoding of Cue-Motivated Behavior via CB1 Receptor Activation in the Ventral Tegmentum

Abstract: SUMMARY Transient increases in nucleus accumbens (NAc) dopamine concentration are observed when animals are presented with motivationally salient stimuli and are theorized to energize reward seeking. They arise from high frequency firing of dopamine neurons in the ventral tegmental area (VTA), which also results in the release of endocannabinoids from dopamine cell bodies. In this context, endocannabinoids are thought to regulate reward seeking by modulating dopamine signaling, although a direct link has never… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
180
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(200 citation statements)
references
References 67 publications
17
180
3
Order By: Relevance
“…We previously demonstrated that the endocannabinoid 2-arachidonoylglycerol, but not anandamide, facilitates dopamine release and cue-motivated behavior (Oleson et al, 2012). In the present study, we replicated this distinction by showing that increased 2-arachidonoylglycerol, but not anandamide, concentrations are sufficient to accelerate the temporal response pattern and induced a negative curvature index in a manner similar to WIN 55 212-2.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…We previously demonstrated that the endocannabinoid 2-arachidonoylglycerol, but not anandamide, facilitates dopamine release and cue-motivated behavior (Oleson et al, 2012). In the present study, we replicated this distinction by showing that increased 2-arachidonoylglycerol, but not anandamide, concentrations are sufficient to accelerate the temporal response pattern and induced a negative curvature index in a manner similar to WIN 55 212-2.…”
Section: Discussionsupporting
confidence: 83%
“…Our endocannabinoid data suggest that ongoing tone might be required to modulate the incentive to forage, while increased concentrations of 2-arachidonoylglycerol might promote the incentive to obtain the primary food source. On the basis of previous data (Melis et al, 2004;Oleson et al, 2012), we speculate that in the latter case, high-frequency firing of dopamine neurons would increase the on-demand synthesis of 2-arachidonoylglycerol, which would then function to amplify dopamine release and ultimately motivate behavior aimed at obtaining the primary food source.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, increased 2-AG signaling in the VTA potentiates cue-evoked increases in the NAc DA and associated reward-seeking (Oleson et al, 2012), and this may participate in the well-known enhancement of cue conditioning that contributes to nicotine reward (Caggiula et al, 2002;Chaudhri et al, 2006). Nicotine-induced elevations in VTA 2-AG were enhanced following repeated drug exposure, and no differences were evident in the 2-AG response to nicotine SA vs YA.…”
Section: Discussionmentioning
confidence: 95%
“…Sub-second changes in DA levels within target regions such as the NAcc are important in reward processing [78,79], and VTA DA stimulation is sufficient to drive intracranial self-stimulation (ICSS) [80,81]. ICSS is also accompanied by increased endocannabinoids that act via CB1 receptors whose blockade reduces the behaviour itself [82,83].…”
Section: Overview (A) Endocannabinoid Role In Dopaminedependent Behavmentioning
confidence: 99%